ANALISIS REAKSI INVESTOR TERHADAP PENERIMAAN LAPORAN OPINI AUDIT GOING CONCERN - Indriani, Widya; Ratmono, Dwi (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to obtain empirical evidence on investor reaction to going concern audit reports. Investor reaction is measured by cumulative  abnormal return (CAR) with the market adjusted model. Institutional ownership is used as a moderating variable. This research hypothesized  that going concern  audit  reports, going  concern  audit reports that cited financing problems,  and going  concern  audit reports  moderated  by institutional  ownership  have negative influence on investor reaction.The sample in this research is all firms listed in Indonesia Stock Exchange during 2008-2013 that received going concern audit reports. The sampling method is purposive sampling, with the final sample is 95 firms. The hypothesis tested using multiple regression with OLS assumptions and one-sample t-test.The result  indicates  going  concern  audit  report  has a significant  negative  influence  on investor reaction. Going concern audit reports that cited financing  problems have no significant influenced  on investor  reaction.  Institutional  ownership  can’t strengthen  the influence  of going concern audit reports on the investor reaction.